Insulation protection composite tape, preparation method and application
By developing a three-layer structure insulating protection composite belt, the problems of poor flexibility and insufficient voltage breakdown strength of the insulating protection materials of new energy vehicles are solved, and the effects of efficient insulation protection and high tensile strength are achieved.
Patent Information
- Application Number
- CN202411451068.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The insulating protection materials of new energy vehicle batteries have problems such as poor flexibility, difficulty in stretching, difficulty in installation, and insufficient voltage breakdown strength.
A three-layer structure insulating protective composite belt has been developed, including glass fiber cloth layer, self-adhesive silicone rubber layer and ceramic silicone rubber layer. Through specific formulation and process treatment, the flexibility, tensile strength of the material is improved and the Flame retardant performance.
It realizes efficient insulation protection of the material, improves the resistance to voltage breakdown, meets the requirements of resistance to high voltage breakdown, and burns at a temperature of 1000℃ for 30 minutes without burning through.
Smart Images

Figure CN118956275B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of insulating protective materials for new energy vehicle batteries, and in particular to an insulating protective composite tape, a preparation method and an application thereof. Background Art
[0002] As an emerging industry in recent years, new energy vehicles have been developing and iterating rapidly, and new energy vehicle batteries, as core components, have always been the focus of the industry to maintain their stability and safety. Among them, the safety of new energy vehicle batteries is particularly important, and the most important thing is the thermal insulation, fire protection and insulation protection performance.
[0003] Currently, mica boards are mostly used on the market, but they lack flexibility, are not easy to stretch, are difficult to install, and have poor voltage breakdown strength. Ceramic liquid silicone rubber, as a new type of fireproof insulation material, is flexible, easy to install, has both thermal insulation and fireproof properties, and has high voltage breakdown strength.
[0004] The insulating protective composite tape product developed by the present invention solves the above-mentioned problems, further improves the voltage breakdown strength, and meets the requirements for high voltage breakdown resistance. Summary of the invention
[0005] The present invention independently develops an insulating protective composite tape, which can be used as a new type of fireproof insulating material in new energy vehicle batteries, plays the role of heat insulation, fire prevention and insulation, and achieves the technical goal of preventing thermal runaway of new energy vehicle batteries.
[0006] An insulating protective composite tape, the insulating protective composite tape has a three-layer structure, the first layer is a glass fiber cloth layer, the second layer is a self-adhesive silicone rubber layer, and the third layer is a ceramic silicone rubber layer, and the self-adhesive silicone rubber layer is arranged between the glass fiber cloth layer and the ceramic silicone rubber layer;
[0007] The self-adhesive silicone rubber layer is formed by curing the self-adhesive silicone rubber. The self-adhesive silicone rubber uses methyl vinyl silicone rubber as a base material, silicon micropowder as a filler, hydroxy silicone oil as a structure control agent, 2,4-dichlorobenzoyl peroxide as a vulcanizing agent, and is added with a tackifier and an organic-inorganic composite flame-retardant insulating composition. The specific formula is: 80-120 parts by weight of methyl vinyl silicone rubber, 1-10 parts by weight of hydroxy silicone oil, 10-60 parts by weight of silicon micropowder, 0.4-3 parts by weight of 2,4-dichlorobenzoyl peroxide, 20-50 parts by weight of an organic-inorganic composite flame-retardant insulating composition, and 5-20 parts by weight of a tackifier;
[0008] The organic-inorganic composite flame-retardant insulating composition comprises an inorganic flame-retardant insulating filler composed of aluminum hydroxide, magnesium hydroxide and aluminum oxide and a flame-retardant silane coupling agent, and the formula thereof is: 30-50wt% aluminum hydroxide, 15-30wt% magnesium hydroxide, 10-30wt% aluminum oxide and 8-25wt% flame-retardant silane coupling agent;
[0009] The flame retardant silane coupling agent is one of flame retardant silane coupling agent I, flame retardant silane coupling agent II and flame retardant silane coupling agent III.
[0010] Preferably, the ceramic silicone rubber layer is formed by curing ceramic liquid silicone rubber, and the ceramic liquid silicone rubber consists of component I and component II;
[0011] The formula of component I is: 80-120 parts by weight of vinyl silicone oil, 20-30 parts by weight of hydrogenated silicone oil, 40-80 parts by weight of ceramic composite powder, 10-20 parts by weight of silicon micropowder and 0.1-1 parts by weight of inhibitor;
[0012] The formula of component II is: 80-120 parts by weight of vinyl silicone oil, 40-80 parts by weight of ceramic composite powder, 10-20 parts by weight of silicon micropowder and 0.01-1 parts by weight of platinum catalyst.
[0013] Preferably, the formula of the ceramic composite powder is: 40-60wt% calcium silicate, 15-25wt% silicon dioxide, 5-10wt% zinc oxide, 10-20wt% MPP flame retardant, 3-8wt% sodium chloroplatinate and 1-4wt% reducing agent.
[0014] Preferably, the insulating protective composite tape has a layer structure of: a glass fiber cloth layer with a thickness of 0.15-0.25 mm, a self-adhesive silicone rubber layer with a thickness of 0.01-0.1 mm, and a ceramic silicone rubber layer with a thickness of 0.25-0.35 mm.
[0015] Preferably, the insulating protective composite tape has a tensile strength of >4MPa, a flame retardancy rating of V-0, an electrical strength of >45kV / mm, and does not burn through when burned at a temperature of 1000°C for 30 minutes.
[0016] A method for preparing an insulating protective composite tape comprises the following steps:
[0017] Step 1, platinum-coating the ceramic composite powder by chemical plating to obtain ceramic composite powder coated with platinum;
[0018] Step 2, according to the formula of component I of ceramic liquid silicone rubber, vinyl silicone oil, hydrogen silicone oil, ceramic composite powder coated with platinum, silicon powder and inhibitor are stirred and mixed by a double-blade vacuum mixer to obtain component I;
[0019] Step 3, according to the formula of component II of ceramic liquid silicone rubber, vinyl silicone oil, the ceramic composite powder coated with platinum prepared in step 1, silicon powder and platinum catalyst are stirred and mixed by a double-blade vacuum mixer to obtain component II;
[0020] Step 4, using a double-blade vacuum mixer to mix and stir 80-100 phr of component I and 80-100 phr of component II to obtain ceramic liquid silicone rubber;
[0021] Step 5, using a flame retardant silane coupling agent to perform surface modification treatment on the inorganic flame retardant insulating filler to obtain an organic-inorganic composite flame retardant insulating composition;
[0022] Step 6, according to the formula of the self-adhesive silicone rubber, methyl vinyl silicone rubber, hydroxy silicone oil, silicon powder, 2,4-dichlorobenzoyl peroxide, the organic-inorganic composite flame-retardant insulating composition prepared in step 5 and the tackifier are stirred and mixed by a double-blade vacuum mixer to obtain the self-adhesive silicone rubber;
[0023] Step 7, press the self-adhesive silicone rubber onto a calender with a press, and evenly apply the self-adhesive silicone rubber to the glass fiber cloth through the calender, then press the ceramicized liquid silicone rubber onto the calender with a press, and evenly apply the ceramicized liquid silicone rubber to the self-adhesive silicone rubber through the calender, and finally place it in an oven for vulcanization and molding to prepare an insulating protective composite tape.
[0024] An insulating protective composite tape prepared according to the above method is used to wrap around the copper busbar of the high-voltage connector in the battery pack of a new energy vehicle to play an insulating and protective role.
[0025] Beneficial effects: The present invention develops a new insulating protective composite tape, which has a three-layer structure, specifically consisting of a ceramic silicone rubber layer, a self-adhesive silicone rubber layer and a glass fiber cloth layer;
[0026] The new insulating protective composite tape product developed by the present invention has a tensile strength of >4MPa, a flame retardant grade of V-0, an electrical strength of >45kV / mm, and does not burn through when burning at a temperature of 1000°C for 30 minutes;
[0027] The present invention, without using mica boards, still meets the technical requirements of the insulation protection composite tape product for resisting high voltage breakdown, thereby solving the technical problems of mica boards used in the insulation protection of new energy vehicle batteries, such as lack of flexibility, difficulty in stretching, and difficulty in installation, and achieves the beneficial technical effect of significantly improving the material's resistance to voltage breakdown. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the product structure diagram of the insulating protective composite tape;
[0029] Among them, 1-glass fiber cloth layer, 2-self-adhesive silicone rubber layer, 3-ceramic silicone rubber layer. DETAILED DESCRIPTION Embodiment 1:
[0030] An insulating protective composite tape, such as Figure 1 As shown, the product structure is: a glass fiber cloth layer 1 with a thickness of 0.2 mm, a self-adhesive silicone rubber layer 2 with a thickness of 0.05 mm, and a ceramic silicone rubber layer 3 with a thickness of 0.3 mm, and the self-adhesive silicone rubber layer 2 is arranged between the glass fiber cloth layer 1 and the ceramic silicone rubber layer 3;
[0031] Among them, the glass fiber cloth layer 1 is 125 (silicone cloth 9), purchased from Suzhou Weidun Composite Cloth Co., Ltd.;
[0032] The ceramic silicone rubber layer 3 is formed by curing ceramic liquid silicone rubber, and the formula of the ceramic liquid silicone rubber is shown in Table 1;
[0033] Table 1 Formulation of ceramic liquid silicone rubber
[0034]
[0035] Note: phr means parts by weight;
[0036] The formula of the ceramic composite powder in Table 1 is: 50wt% calcium silicate (700 mesh), 20wt% silicon dioxide (1200 mesh), 8wt% zinc oxide (1500 mesh), 14wt% MPP flame retardant, 6wt% sodium chloroplatinate and 2wt% reducing agent (formaldehyde); wherein the MPP flame retardant is melamine polyphosphate, purchased from Dongguan Xingyuan Chemical Co., Ltd.;
[0037] The self-adhesive silicone rubber layer 2 is formed by curing the self-adhesive silicone rubber. The specific composition of the self-adhesive silicone rubber is: methyl vinyl silicone rubber as a base material, silicon powder as a filler, hydroxy silicone oil as a structure control agent, 2,4-dichlorobenzoyl peroxide as a vulcanizing agent, and an added tackifier and an organic-inorganic composite flame-retardant insulating composition. The specific formula is shown in Table 2 below;
[0038] Table 2 Formula of self-adhesive silicone rubber
[0039]
[0040] The formula of the organic-inorganic composite flame-retardant insulating composition in Table 2 is: 35wt% aluminum hydroxide (1000 mesh), 25wt% magnesium hydroxide (1000 mesh), 20wt% aluminum oxide and 20wt% flame-retardant silane coupling agent;
[0041] Among them, alumina was purchased from Hangzhou Hengge Nanotechnology Co., Ltd., model HN-L600D;
[0042] The flame retardant silane coupling agent is one of flame retardant silane coupling agent I, flame retardant silane coupling agent II, and flame retardant silane coupling agent III;
[0043] The chemical structure and preparation method of flame retardant silane coupling agent I are recorded in Experimental Example I; the chemical structure and preparation method of flame retardant silane coupling agent II are recorded in Experimental Example II; the chemical structure and preparation method of flame retardant silane coupling agent III are recorded in Experimental Example III. Embodiment 2:
[0044] The preparation method of an insulating protective composite tape in Example 1 is as follows:
[0045] Step 1: Platinum coating the ceramic composite powder by chemical plating. The specific preparation process is as follows:
[0046] (1) Preparation of ceramic composite powder: According to the formula of ceramic composite powder, calcium silicate, silicon dioxide, zinc oxide and MPP flame retardant were mixed in a powder mixer to obtain ceramic composite powder, which was then ultrasonically cleaned in methanol, 0.1 mol / L sodium hydroxide solution and 0.1 mol / L hydrochloric acid solution for 15 min to remove surface contamination, then ultrasonically cleaned in deionized water for 30 min and vacuum dried for 2 h;
[0047] (2) Platinum coating of ceramic composite powder: add the formulated amount of sodium chloroplatinate and deionized water (the amount of deionized water is 10 times the total weight of the ceramic composite powder) to the ceramic composite powder prepared in step (1), stir and mix at 1500 rpm for 30 min using a high-speed stirrer, then add the formulated amount of formaldehyde (reducing agent), continue stirring and reacting at 1500 rpm for 1 h, filter, and dry at 120° C. for 2 h to obtain a ceramic composite powder coated with platinum;
[0048] Step 2: According to the formula of component I in Table 1, vinyl silicone oil, hydrogenated silicone oil, the ceramic composite powder coated with platinum prepared in step 1, silicon powder and inhibitor were stirred and mixed by a double-blade vacuum mixer at 1000 rpm for 1 hour to prepare component I;
[0049] According to the formula of component II in Table 1, vinyl silicone oil, the ceramic composite powder coated with platinum prepared in step 1, silicon powder and platinum catalyst were stirred and mixed by a double-blade vacuum mixer at 1000 rpm for 1 hour to prepare component II;
[0050] Step 3: Use a double-blade vacuum mixer to mix and stir 100 phr of component I and 100 phr of component II to prepare ceramic liquid silicone rubber. The stirring speed of the double-blade vacuum mixer is 1500 rpm and the stirring time is 2 hours.
[0051] Step 4: Prepare an organic-inorganic composite flame-retardant insulating composition I: Use a flame-retardant silane coupling agent I to perform surface modification treatment on an inorganic flame-retardant insulating filler (aluminum hydroxide, magnesium hydroxide and aluminum oxide), and the specific steps are: prepare the ingredients according to the formula of the organic-inorganic composite flame-retardant insulating composition, add aluminum hydroxide, magnesium hydroxide, aluminum oxide and a mixed solvent (anhydrous ethanol / deionized water, V / V, 7:3, the amount of the solvent is 10 times the total weight of aluminum hydroxide, magnesium hydroxide and aluminum oxide) into a round-bottom flask, ultrasonically mix for 30 minutes, stir at room temperature for 2 hours (stirring speed: 700rpm), then add the formulated amount of flame-retardant silane coupling agent I and 2 drops of glacial acetic acid to the flask in sequence, heat to 60°C, use a high-speed stirrer to stir the reaction at 800rpm for 2 hours, filter, repeatedly wash with ethanol, and dry at 120°C for 1 hour;
[0052] Step 5: According to the formula in Table 2, methyl vinyl silicone rubber, hydroxy silicone oil, silicon powder, 2,4-dichlorobenzoyl peroxide, the organic-inorganic composite flame-retardant insulating composition I prepared in step 4 and the tackifier are stirred and mixed at 1000 rpm for 1 hour by a double-blade vacuum mixer to prepare a self-adhesive silicone rubber;
[0053] Step 6: Press the self-adhesive silicone rubber onto a calender with a press, and evenly apply the self-adhesive silicone rubber to the 0.2mm glass fiber cloth through the calender, with a coating speed of 2m / min and a coating thickness of 0.05mm; then press the ceramicized liquid silicone rubber onto the calender with a press, and evenly apply the ceramicized liquid silicone rubber to the self-adhesive silicone rubber through the calender, with a coating speed of 1.5m / min and a coating thickness of 0.3mm; finally, place it in a 140°C oven for vulcanization (vulcanization time is 10min), and prepare the insulating protective composite tape I;
[0054] The insulating protective composite tape II is prepared. The difference between the preparation method and experimental steps of the insulating protective composite tape I is that the flame retardant silane coupling agent II is used to replace the flame retardant silane coupling agent I.
[0055] The insulating protective composite tape III is prepared. The difference between its preparation method and experimental steps and those of the insulating protective composite tape I is that the flame retardant silane coupling agent III is used to replace the flame retardant silane coupling agent I.
[0056] Comparative Example:
[0057] An insulating protective composite tape is prepared, and the preparation method and experimental steps thereof are different from those of the insulating protective composite tape I only in that the self-adhesive silicone rubber layer 2 is not contained.
[0058] Performance Test:
[0059] (1) Test the electrical strength of the sample in accordance with GB / T 1408.1-2016;
[0060] (2) Test the flame retardancy level of the samples according to GB / T10707-2008 standard;
[0061] (3) The static mechanical properties of the samples were tested using a universal material testing machine in accordance with GB / T528-2009 standard, with a loading speed of 500 mm / min;
[0062] (4) Combustion test: Maintain the temperature at 1000°C for 30 minutes and observe whether the sample is burned through;
[0063] The test results of each insulating protective composite tape sample are shown in Table 3;
[0064] Table 3 Performance test results of insulation protection composite tape
[0065]
[0066] From the experimental results in Table 3, the following conclusions are obtained:
[0067] Conclusion 1: The insulating protective composite tape product developed by the present invention does not use mica board, but still meets the technical requirements of insulating protective composite tape products for resisting high voltage breakdown, and has achieved the beneficial technical effect of significantly improving the material's voltage breakdown strength;
[0068] Conclusion 2: In the insulating protective composite tape, if the self-adhesive silicone rubber layer 2 is omitted, its comprehensive performance will be significantly reduced, especially the insulation performance and flame retardant performance will be reduced significantly.
[0069] Experimental Example I:
[0070] Preparation of flame-retardant silane coupling agent I: Based on the nucleophilic substitution reaction mechanism, the carboxyl functional group of 1H-1,2,4-triazole-3-carboxylic acid and the mercapto functional group of 3-mercaptopropyltrimethoxysilane were catalyzed by p-toluenesulfonic acid to undergo a thioesterification reaction to prepare flame-retardant silane coupling agent I, whose chemical structure is:
[0071] ;
[0072] The specific experimental steps of flame retardant silane coupling agent I are as follows: under mechanical stirring conditions, 1.2 g of 1H-1,2,4-triazole-3-carboxylic acid, 2.0 g of 3-mercaptopropyltrimethoxysilane, 1.0 g of p-toluenesulfonic acid and 50 mL of anhydrous tetrahydrofuran are added to a three-necked flask with a water separator, the temperature is raised to 80° C. and stirred for reaction for 5 h, the solvent is removed by rotary evaporation, and the agent is washed with saturated sodium bicarbonate aqueous solution and deionized water in turn until neutral, filtered, and vacuum dried to obtain flame retardant silane coupling agent I;
[0073] The nuclear magnetic resonance hydrogen spectrum of flame retardant silane coupling agent I is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.79-0.82 (t, 2H), 1.78-1.85 (m, 2H), 3.11-3.14 (t, 2H), 3.56 (s, 9H), 8.24 (s, 1H).
[0074] Experimental Example II:
[0075] Preparation of flame retardant silane coupling agent II: Based on the Kabachnik-Fields reaction mechanism, flame retardant silane coupling agent I, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and polyformaldehyde undergo condensation reaction to generate flame retardant silane coupling agent II, whose chemical structure is:
[0076] ;
[0077] The specific experimental steps of flame retardant silane coupling agent II are as follows: add 1.1g DOPO, 1.5g flame retardant silane coupling agent I, 0.2g polyformaldehyde, 20mL ethanol and 20mL anhydrous tetrahydrofuran into a four-necked bottle, stir at room temperature until all are dissolved, heat to 70°C under nitrogen protection and mechanical stirring for 2h, cool to room temperature, filter, wash with ethanol, and vacuum dry to obtain flame retardant silane coupling agent II;
[0078] The nuclear magnetic resonance hydrogen spectrum of flame retardant silane coupling agent II is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.85-0.88 (t, 2H), 1.79-1.86 (m, 2H), 3.03-3.06 (t, 2H), 3.57 (s, 9H), 5.12-5.15 (d, 2H), 7.35-7.90 (m, 8H), 8.19 (s, 1H).
[0079] Experimental Example III:
[0080] Preparation of flame retardant silane coupling agent III, the preparation process is as follows:
[0081] Step 1: Based on the Kabachnik-Fields reaction mechanism, 2-chloro-4,6-bis(ethylamino)-1,3,5-triazine, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and polyformaldehyde undergo a condensation reaction to generate a chloro-DOPO-based triazine monomer, and the amount ratio of 2-chloro-4,6-bis(ethylamino)-1,3,5-triazine, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and polyformaldehyde participating in the reaction is controlled to be 1:(2.01-2.09):(3.01-3.5), preferably 1:2.05:3.33, and its chemical structure is:
[0082] ;
[0083] Step 2: Using 3-aminopropyltrimethoxysilane as a nucleophilic reagent, triethylamine is used to catalyze the nucleophilic substitution reaction between the chlorine functional group of the chlorine-based DOPO triazine monomer and the amino functional group of 3-aminopropyltrimethoxysilane to generate a flame-retardant silane coupling agent III, whose chemical structure is:
[0084] ;
[0085] The specific experimental steps for preparing flame retardant silane coupling agent III are as follows:
[0086] Add 2.0 g 2-chloro-4,6-bis(ethylamino)-1,3,5-triazine, 4.4 g DOPO, 1.0 g paraformaldehyde, 40 mL ethanol and 40 mL anhydrous tetrahydrofuran into a four-necked bottle, stir at room temperature until all dissolved, heat to 70° C. and reflux for 6 h under nitrogen protection and mechanical stirring, cool to room temperature, filter, wash with ethanol, and vacuum dry to obtain a chloro-DOPO-based triazine monomer;
[0087] 3.3 g of chloro-DOPO-triazine monomer and 30 mL of anhydrous tetrahydrofuran were added to a three-necked flask, stirred at room temperature until completely dissolved, then 1.0 mL of 3-aminopropyltrimethoxysilane and 0.8 mL of triethylamine were added to the three-necked flask in sequence, the temperature was raised to 40° C., stirred for reaction for 6 h, filtered, washed with deionized water and ethanol in sequence, and vacuum dried to obtain flame-retardant silane coupling agent III;
[0088] The nuclear magnetic resonance hydrogen spectrum of flame retardant silane coupling agent III is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 1H NMR(CDCl3,400MHz) δ:0.66-0.69(t,2H),1.34-1.38(t,6H),1.82-1.89(m,2H),3.57(s,9H),3.65-3.71(m,4H),3.80-3.83(t,2H),4.50-4.62(m,4H),7.26-8.14(m,16H)。
Claims
1. An insulating protective composite tape, characterized in that: The insulating protective composite tape has a three-layer structure, the first layer is a glass fiber cloth layer, the second layer is a self-adhesive silicone rubber layer, and the third layer is a ceramic silicone rubber layer. The self-adhesive silicone rubber layer is arranged between the glass fiber cloth layer and the ceramic silicone rubber layer. The self-adhesive silicone rubber layer is formed by curing the self-adhesive silicone rubber, and the formula of the self-adhesive silicone rubber is: 80-120 parts by weight of methyl vinyl silicone rubber, 1-10 parts by weight of hydroxy silicone oil, 10-60 parts by weight of silicon powder, 0.4-3 parts by weight of 2,4-dichlorobenzoyl peroxide, 20-50 parts by weight of an organic-inorganic composite flame-retardant insulating composition, and 5-20 parts by weight of a tackifier; The formula of the organic-inorganic composite flame-retardant insulating composition is: 30-50wt% aluminum hydroxide, 15-30wt% magnesium hydroxide, 10-30wt% aluminum oxide and 8-25wt% flame-retardant silane coupling agent; The flame retardant silane coupling agent is one of flame retardant silane coupling agent I, flame retardant silane coupling agent II, and flame retardant silane coupling agent III; The chemical structural formula of the flame retardant silane coupling agent I is: ; The chemical structural formula of the flame retardant silane coupling agent II is: ; The chemical structural formula of the flame retardant silane coupling agent III is: ; The ceramic silicone rubber layer is formed by curing ceramic liquid silicone rubber, and the ceramic liquid silicone rubber consists of component I and component II; The formula of component I is: 80-120 parts by weight of vinyl silicone oil, 20-30 parts by weight of hydrogenated silicone oil, 40-80 parts by weight of ceramic composite powder, 10-20 parts by weight of silicon micropowder and 0.1-1 parts by weight of inhibitor; The formula of component II is: 80-120 parts by weight of vinyl silicone oil, 40-80 parts by weight of ceramic composite powder, 10-20 parts by weight of silicon micropowder and 0.01-1 parts by weight of platinum catalyst; The formula of the ceramic composite powder is: 40-60wt% calcium silicate, 15-25wt% silicon dioxide, 5-10wt% zinc oxide, 10-20wt% MPP flame retardant, 3-8wt% sodium chloroplatinate and 1-4wt% reducing agent.
2. The insulating protective composite tape according to claim 1, characterized in that: The layer structure of the insulating protective composite tape is: a glass fiber cloth layer with a thickness of 0.15-0.25 mm, a self-adhesive silicone rubber layer with a thickness of 0.01-0.1 mm, and a ceramic silicone rubber layer with a thickness of 0.25-0.35 mm.
3. The insulating protective composite tape according to claim 1, characterized in that: The insulating protective composite tape has a tensile strength of >4MPa, a flame retardant grade of V-0, an electrical strength of >45kV / mm, and does not burn through when burned at a temperature of 1000°C for 30 minutes.
4. The method for preparing an insulating protective composite tape according to claim 1, characterized in that: The following steps are involved: Step 1, platinum-coating the ceramic composite powder by chemical plating to obtain ceramic composite powder coated with platinum; Step 2, according to the formula of component I of ceramic liquid silicone rubber, vinyl silicone oil, hydrogen silicone oil, ceramic composite powder coated with platinum, silicon powder and inhibitor are stirred and mixed by a double-blade vacuum mixer to obtain component I; Step 3, according to the formula of component II of ceramic liquid silicone rubber, vinyl silicone oil, the ceramic composite powder coated with platinum prepared in step 1, silicon powder and platinum catalyst are stirred and mixed by a double-blade vacuum mixer to obtain component II; Step 4, using a double-blade vacuum mixer to mix and stir 80-100 phr of component I and 80-100 phr of component II to obtain ceramic liquid silicone rubber; Step 5, using a flame retardant silane coupling agent to perform surface modification treatment on an inorganic flame retardant insulating filler to obtain an organic-inorganic composite flame retardant insulating composition; wherein the inorganic flame retardant insulating filler is composed of aluminum hydroxide, magnesium hydroxide and aluminum oxide; Step 6, according to the formula of the self-adhesive silicone rubber, methyl vinyl silicone rubber, hydroxy silicone oil, silicon powder, 2,4-dichlorobenzoyl peroxide, the organic-inorganic composite flame-retardant insulating composition prepared in step 5 and the tackifier are stirred and mixed by a double-blade vacuum mixer to obtain the self-adhesive silicone rubber; Step 7, press the self-adhesive silicone rubber onto a calender with a press, and evenly apply the self-adhesive silicone rubber to the glass fiber cloth through the calender, then press the ceramicized liquid silicone rubber onto the calender with a press, and evenly apply the ceramicized liquid silicone rubber to the self-adhesive silicone rubber through the calender, and finally place it in an oven for vulcanization and molding to prepare an insulating protective composite tape.
5. The use of an insulating protective composite tape according to any one of claims 1 to 3, characterized in that: The insulating protective composite tape is wrapped around the high-voltage connector copper busbar in the battery pack of new energy vehicles to provide insulation protection.
Citation Information
Patent Citations
DOPO-based flame retardant, and preparation method thereof
CN106243385A
Ceramic silicone rubber composite belt with mica layer and preparation method of ceramic silicone rubber composite belt
CN113402993A